KRITIK TERHADAP EPISTEMOLOGI UNIVERSAL DECLARATION OF HUMAN RIGHTS: PERSPEKTIF ISLAM - Afdal Afdal; Waston Waston (Universitas Muhammadiyah Surakarta, 2015)
Since established, Universal Declaracion of Human Rights (UDHR) upheldas a global value by all the countries in the world. UDHR through the UN as a referenceas a common standard for measuring the level of success of a country in upholdinghuman rights. How this study focus on the implications of the secular epistemologyagainst the substance of the Universal Declaration Of Human Rights? and How doesIslam look at epistemology Universal Declaration Of Human Rights? To answer thesequestions used the data of literature with a philosophical approach as research methodsand using several analytical tools such as interpretation, induction and deduction,internal coherence, holistika and description. Results from this study indicate that thesecular epistemology epistemology UDHR as the foundation material implicationsfor cargo. Substance of the UDHR can be translated very freely and without limitvalues mengabaiakan even religiosity. Humans are considered as central, source anddestination at the same time the fi nal orientation of each human behavior. Religionand God are not regarded as something sacred, but only considered as a complement tohuman life into the realm of free privatization adopted or not by each individual. Such aview is contrary to Islam. Islam holds that religion and God is something that is sacredand can not be separated from every facet of human life. God is central, as well as sourceand destination end orientation every human behavior.Keywords: epistemology; human rights; the Islamic human rights.